Radion-Higgs mixing effects on bounds from LHC Higgs boson searches - de Sandes, Hiroshi; Rosenfeld, Rogério [UNESP] (Amer Physical Soc, 2012)
The radion, a scalar particle associated with the radius of a compact warped extra dimension, may be the lightest new particle in this class of models. Its couplings to SM particles are proportional to the their masses, similar to the usual Higgs boson, but suppressed by a scale Lambda(r), the radion vacuum expectation value. The main differences are the coupling to massless gauge bosons that receives contribution from the trace anomaly of the energy-momentum tensor due to the nonvanishing beta functions and the mixing with the Higgs boson arising from a nonminimal coupling to gravity parametrized by a dimensionless coefficient xi. In particular, these differences can result in significant modifications of the radion phenomenology. We use current LHC data on Higgs searches to find exclusion regions on the parameters of a radion model, Lambda(r), xi and the radion mass m(r). We find that, even for low values of Lambda(r), the radion can still have a mass in the region where the Standard Model Higgs has been excluded, for a narrow range of values for the mixing parameter. Some signals at the LHC for this scenario are discussed. We also find that it is possible to hide the Higgs boson in the current searches in this model, due to a suppression of its couplings.